Nano βθ-Open Sets in Nano Topological Spaces - Rzgar U. Ahmad; Sami A. Hussein (Tikrit Journal of Pure Science)
This paper's primary objective is to present and study a different class of nano sets known as nano βθ-open sets in nano topological spaces. Additionally, introduced some nano topological concepts by using nano βθ-open set.